Transient ion-mediated interactions regulate subunit rotation in a eukaryotic ribosome - George Wanes; Udayan Mohanty; Paul C. Whitford (Proceedings of the National Academy of Sciences, 2026)
While it is well known that ion binding can stabilize RNA structure, little is known about how transient/probabilistic ionic interactions facilitate biologically relevant conformational rearrangements. To address this, we developed a theoretical model that employs all-atom resolution with a simplified representation of biomolecular energetics (i.e., a structure-based “SMOG” model), explicit electrostatics, and ions (K + , Cl − , Mg 2+ ). For well-studied RNA systems, the model accurately describes the concentration-dependent ionic environment, which includes chelated and hydrated/diffuse ions. With this foundation, we applied the model to simulate the yeast ribosome and quantified the ion-dependent energy landscape of intersubunit rotation. These calculations show how millimolar increases in [MgCl 2 ] shift the energetics to favor the unrotated state. The free-energy barrier is also increased, leading to an order-of-magnitude reduction in kinetics that is correlated with formation of ion-mediated interactions between the subunits. This provides a physical description for how transient ionic interactions can contribute to large-scale biomolecular dynamics.